2012
DOI: 10.4141/cjps2011-169
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cultivar, seeding rate and applied nitrogen onBrassica carinataseed yield and quality in contrasting environments

Abstract: Pan, X., Caldwell, C. D., Falk, K. C. and Lada, R. 2012. The effect of cultivar, seeding rate and applied nitrogen on Brassica carinata seed yield and quality in contrasting environments. Can. J. Plant Sci. 92: 961–971. The unremitting growth of oilseed demand makes it necessary to explore alternative oilseed crops to meet this requirement. This study evaluated the effects of genotype, seeding rate and nitrogen (N) supply on the seed yield and quality of oilseed Brassica carinata A. Braun in three contrasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
72
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 28 publications
(23 reference statements)
15
72
2
Order By: Relevance
“…When the rankings were average across all sites for 2013 and 2014, the two common commercial lines of canola, DK3042 (DeKalb) and Invigor L130 (Bayer Crop Sciences) tended to be the highest ranking in yield performance. The B. carinata cultivar 080814 EM also performed well indicating that significant progress is being made in its development as a biofuel feedstock for North America (Pan et al, 2012). Conversely, the S. alba cultivar Idagold and B. napus cultivar Gem were consistently low yielding across sites.…”
Section: Seed and Biomass Yieldsmentioning
confidence: 92%
See 3 more Smart Citations
“…When the rankings were average across all sites for 2013 and 2014, the two common commercial lines of canola, DK3042 (DeKalb) and Invigor L130 (Bayer Crop Sciences) tended to be the highest ranking in yield performance. The B. carinata cultivar 080814 EM also performed well indicating that significant progress is being made in its development as a biofuel feedstock for North America (Pan et al, 2012). Conversely, the S. alba cultivar Idagold and B. napus cultivar Gem were consistently low yielding across sites.…”
Section: Seed and Biomass Yieldsmentioning
confidence: 92%
“…However, B. carinata, which has more recently undergone development as a biofuel feedstock in North America performed as well or better than the B. napus and B. juncea genotypes in the present study. Similarly, Pan et al (2012) reported that several recently developed B. carinata cultivars preformed as well or better than a common commercial line of B. juncea (AC Vulcan) across a diversity of environments in Canada. Conversely, Blackshaw et al (2011) found that B. carinata did not perform as well as several other Brassica species in the Prairie Province region of Canada.…”
Section: Seed and Biomass Yieldsmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, improvement of N fertilizer management is important, which requires an understanding of crop responses to different levels of fertilizer in different agroecosystems (Pilorgé et al, 2006). Some reports show that carinata seed yield increases with increasing N rate up to 150 kg N ha −1 (Pan et al, 2012). Some reports show that carinata seed yield increases with increasing N rate up to 150 kg N ha −1 (Pan et al, 2012).…”
mentioning
confidence: 99%